Evaluation of uncertainty parameters in risk assessment of agricultural chemicals on groundwater contamination. (15th December 2009) - Inoue, Kazuya; Tanaka, Tsutomu; Setsune, Naoko
Risk assessment is meaningful to quantitatively define adverse effects on human health and natural environment and it is possible to choose the most effective action related to groundwater contamination. In this paper, parameter uncertainties in risk assessment in geo-environmental system are examined through a probabilistic application of deterministic contaminant transport model using Latin hypercube sampling. One of the agricultural chemicals, 1, 3-dichloropropene, is of concern to simulate its fate released from a line source in a two-dimensional homogeneous aquifer. The results indicate that the degree of the effect of parameter uncertainty is spatially different at exposure points and the dispersivity and the retardation factor are influential parameters to risk values while the water ingestion rate and the reduction factor of contaminant source play small roles in predicting the risk. Furthermore, it is found that the parameter uncertainty should be addressed in risk assessment procedures for groundwater contamination associated with agricultural chemicals.